Territorial moments of an informal settlement: a methodological proposal - Mejía Ayala, Wladimir (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The “territorial moments of an informal settlement” methodology is proposed based on how different actors understand the informal settlement phenomenon. This methodologywas built on the basis of tourism geography theories without referring to that socioeconomic activity. From the implementation of an exercise conducted between 2017 and 2018, the characteristics of each moment are presented: origin, beginning, development, stagnation, and future.The results show that the methodological tool proposed allows to value the experiences of an informal settlement and understand each of its moments, from the difficulties experiencedby its inhabitants to the opportunities they found to solve some problems and build their own living space.